Subjective answer marking system using text processing technique / Radin Arini Radin Mohd Mokhtar - Radin Mohd Mokhtar, Radin Arini (2022)
Since pandemic of Covid-19, it has driven institution to make Online Distance Learning, which lecturers and students need to communicate through online platforms such as smartphone, laptop and PCs. Students need to take all the assessment such as test, quiz and also final examination to be evaluated even in this pandemic situation. It is a compulsory to be examined. Hence, to mark all of the student's assessment using automated approach is better than manual marking. This study aims to develop a web- based system that can assists marking on subjective answers using keyword extraction. The system is developed and utilized by python and also flask micro web framework. The key words similarity being tested to compare with the student's answer and answer scheme. The marks from the automated evaluation and manual evaluation by the lecturer were being compared and the differences were taken. The results of the automated marks are approximately the same by the manual marking.